LUIZA OLANDER – A UKRAINIAN SCHOLAR OF THE WORKS OF THE POLISH WRITERS OF THE TWENTIETH AND THE TWENTIETH-FIRST CENTURIES - Kravchenko, Svitlana (Prace Polonistyczne, 2022)
The article presents the famous Ukrainian scholar Luiza Olander, who has for many years been thoroughly researching the phenomena, characters, and processes that can be found in Polish literature. She is the author of many dissertations in which she used various (historical, literary, comparative, biographical, and structural) methods to analyze literary phenomena. In her work, Olander uses and develops the concepts of the European founders of semiotics and structuralism. Because of her long-term biographical connection with Volhynia, she has paid special attention to writers from the cultural borderland and examined their works from a comparative perspective. In Olander’s work, the most outstanding figures of Polish literature are considered in a very broad European cultural context.